How to Handle Glyphosate-Related Fruit Drop - Kanissery, Ramdas; Alferez, Fernando; Batuman, Ozgur (EDIS, 2018)
In spite of being the most widely used and effective herbicide in citrus, there is an increasing concern among the growers that glyphosate may be one of the various reasons behind the premature fruit drop in citrus. Improper spray applications directed to the tree canopy will result in herbicide contact with the fruits and immature fruit drop in citrus. Maintaining a safe spray boom distance and positioning the angle of OC nozzles during the sensitive (near fruit maturity) periods will help to reduce the fruit drop from direct spray contacts. Preliminary studies conducted at Southwest Florida REC show that fruit detachment force (FDF) in citrus is affected by glyphosate in a dose-dependent manner. This article is intended to provide insights into glyphosate linked fruit drop in citrus and its management.